MIR4435-2HG Is a Potential Pan-Cancer Biomarker for Diagnosis and Prognosis - Zhong, Chenming; Xie, Zijun; Zeng, Ling-hui; Yuan, Chunhui; Duan, Shiwei (Frontiers in Immunology, 2022)
The lncRNA MIR4435-2 host gene (MIR4435-2HG) is located on human chromosome 2q13, and its expression is up-regulated in 18 tumors. MIR4435-2HG participates in 6 signaling pathways to promote tumorigenesis, including the TGF-β signaling pathway, Wnt/β-catenin signaling pathway, MDM2/p53 signaling pathway, PI3K/AKT signaling pathway, Hippo signaling pathway, and MAPK/ERK signaling pathway. MIR4435-2HG competitively binds with 20 miRNAs to form a complex ceRNA network, thereby regulating the expression of downstream target genes. The high expression of MIR4435-2HG is also closely related to the clinicopathological characteristics and poor prognosis of a variety of tumors. Also, the high expression of MIR4435-2HG in peripheral blood or serum has the value of predicting the risk of 9 tumors. In addition, MIR4435-2HG participates in the mechanism of action of three cancer drugs, including resveratrol for the treatment of lung cancer, cisplatin for non-small cell lung cancer and colon cancer, and carboplatin for triple-negative breast cancer. This article systematically summarizes the diagnostic and prognostic value of MIR4435-2HG in a variety of tumors and outlines the ceRNA network and signaling pathways related to MIR4435-2HG, which will provide potential directions for future MIR4435-2HG research.